Rentabilidad financiera del producto leche saborizada de la Cooperativa de Producción Agropecuaria Chone LTDA. - Hidrovo Zambrano, Ángela Verónica (2010)
The this is en titled Financial Return Flavored Milk Product of Chone Farming Cooperative Ltd., is the result of an investigation conducted to traders, who se business is the production of milk in Canton Chone, and so does marketing products identical to that of flavored milk, the subject of this study and finally as practicable, workable and cost-effective production of flavored milk by an investment project implemented by the Agricultural Production Cooperative Chone Ltda, with funding from a contribution non-refundable by the Ministry of Social and Economic Inclusion of $ 254,876.00 equivalent to 76.42% of total invest mental so aims to create 12 places of work and at least 10 jobs in directly, the acquisition is about 40.000 liters of milk and making an index of value added of 65% in monthly production, which shows that forever y dollar invested dollar 0.65 for the value added in the production process.